(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This article explores the linguistic features of antonymic relations observed in interior design terminology. The study analyzes terminological oppositions formed within semantic fields such as stylistic approaches, material treatment, color concepts, and spatial planning. Using descriptive, structural-semantic, and comparative methods, the research identifies semantic differences and functional similarities between antonymic terms used in English and Uzbek. Furthermore, the stylistic connotation and communicative role of these terms in design-related texts are examined in practice. The article theoretically and practically substantiates the role of antonymy in understanding the conceptual foundations of interior design language.